Controversies in the Treatment of Cardiac Sarcoidosis - Obi, Ogugua Ndili; Lower, Elyse E.; Baughman, Robert P. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
There are many challenging aspects of the management of cardiac sarcoidosis (CS) with corticosteroids and other immunosuppressive therapy ( IST). First, it is not always clear who will benefit from therapy or when to initiate treatment. Secondly, there are no randomized controlled trials or large prospective studies to guide what medications to use, at what doses, for how long.The European Respiratory Society (ERS) clinical practice guidelines on the treatment of sarcoidosis makes a strong recommendation for the use of immunosuppressive therapy in CS patients with functional cardiac abnormalities, including heart blocks, dysrhythmias, or cardiomyopathy where patients are considered at-risk of adverse outcomes.Corticosteroids are the first line immunosuppressive therapy in CS however, early initiation of second-line steroid sparing medications has been advocated and there is data to suggest that concomitant initiation of therapy may be more beneficial. The use of anti-tumour necrosis factor (anti-TNF) antagonists (including infliximab and adalimumab) considered beneficial third-line anti-sarcoidosis treatment agents in other severe refractory manifestations of disease remains controversial.